The effect of a synthetic double layer hydroxide on the rate of II→I phase transformation of poly(1-butene) - V. Causin; C. Marega; A. Marigo; R. Saini; G. Ferrara; R. Neppalli (eXPRESS Polymer Letters, 2011)
Perkalite is an unusual clay in the domain of polymer-based nanocomposites. In this paper, the use of perkalite as a filler for poly(1-butene) was investigated. Particular attention was posed on the study of the effect of this particular kind of clay on the rate of II→I phase transition of the matrix. Wide angle X-ray diffraction (WAXD), small angle X-ray scattering (SAXS), transmission electron microscopy (TEM) and differential scanning calorimetry (DSC) were used to determine the structure and morphology of the samples, the degree of dispersion of the filler and to follow the kinetics of the phase transition of poly(1-butene). Mechanical properties were moreover measured. Perkalite was found to increase the rate of II→I phase transition with respect to the neat matrix, because it affected the free energy of the crystalline phase, by decreasing the perfection of the crystals. Rather than the disruption of the regular ordering at a crystalline cell level, the effect on the lamellar morphology seems to be preponderant. The fragility of perkalite layers and the substantial reduction of the tactoids did not allow to influence the entropic factor to the phase diagram of poly(1-butene), because the filler was not able to locally increase the pressure on the nascent crystalline domains. Perkalite was therefore not able to achieve a direct formation of the phase I of poly(1-butene) directly from the melt. The reduction of the size of perkalite tactoids confirmed that poly(1-butene) is very efficient in homogeneously dispersing the filler, thereby justifying the use of the materials produced in the present study as viable masterbatches for the production of polyolefin-based nanocomposites.